Hydrometeorological hazards on radiation contaminated territories of the East Ural region of Russia - Victor Vladimirovich Razumov; Natalia Victorovna Razumova (Наука. Инновации. Технологии, 2022)
In work possibility of influence of the dangerous hydrometeorological phenomena on character and scales of distribution of radioactive pollution of environment within radiation polluted areas is shown. The analysis of existential distribution the ushcherboopasnykh of the hydrometeorological phenomena in radiation polluted territories of the East Ural region of Russia (The Chelyabinsk, Kurgan and Sverdlovsk regions) is carried out. The most part, the occurred for 1991-2013, such phenomena has been connected with strong winds, hurricanes and tornadoes, and also with heavy rains and heavy rains that, in our opinion, substantially promoted distribution of radioactive materials across the territory of the region. Most often these phenomena happened on the territory of Chelyabinsk region which is the most radiation polluted. The quantitative characteristic of the happened emergency situations caused by the dangerous hydrometeorological phenomena which generally arose during the spring and summer period is given.